The influence of different hardness of the tool material on the wear of SHM grinding wheels and the specific energy intensity of grinding - Lavrinenko, Valerii; Solod, Volodymyr; Tyshchenko, Volodymyr; Ostroverkh, Yevgeniy (Національний технічний університет "Харківський політехнічний інститут", 2024)
It was established that conditionally viscous-brittle tool materials (high-speed steels and hard alloys) behave in the same way with an increase in hardness: wheel wear and the specific energy consumption of their grinding decrease. As the hardness of brittle tool oxide-carbide ceramics increases, both wheel wear and the specific energy consumption of grinding, on the contrary, increase. That is, an increase in the hardness of viscous-brittle materials facilitates the separation of elementary chips, less energy is needed for this, and accordingly the wear of the wheel and the specific energy consumption of their grinding are reduced. On brittle ceramics, with increasing hardness, there is no change in chip removal, but harder sludge becomes more abrasive and, as a result, the wear of the wheel and the specific energy consumption of their grinding increase. The conclusion from the literature that hard and less plastic materials require relatively less specific energy for grinding is confirmed by us when comparing materials of approximately the same hardness - hard alloys and ceramics. In ceramics, the energy consumption of grinding is actually four times lower than that of hard alloys.

Для різального інструменту визначальну роль відіграє твердість матеріалу інструменту. Водночас це впливає на їх технологічність, хоча є певні особливості. Так, твердість кераміки на основі нітриду кремнію і карбіду кремнію має менший вплив на їх оброблюваність, ніж щільність, а при шліфуванні загартованих сталей сила різання не залежить від їх твердості. Твердість жароміцних інструментальних сталей визначається дисперсністю і кількістю карбідів, що виділяються при відпусканні, і залишкового аустеніту в якості м'якого компонента. Аж до показника твердості інструментальних сталей 65 HRC, зі збільшенням твердості зростає і їх міцність. Однак їх висока твердість відповідає різкому зниженню в'язкості. Саме тому певний інтерес можуть представляти дослідження впливу показника твердості на оброблюваність матеріалу інструменту, коли змінюється твердість на одному матеріалі.
Вплив різної твердості інструментального матеріалу на знос шліфувальних кругів з НТМ та питому енергоємність шліфування
Keywords: hardness; high-speed steels; hard alloys; ceramics; wear of SHM grinding wheels; specific energy intensity of processing; твердість; швидкорізальні сталі; тверді сплави; кераміка; знос шліфувальних кругів з НТМ; питома енергоємність обробки